Reading the February Revolution - David, Randolf S. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
The February events in the Philippines have been referred to with some degree of ambiguity and indecision. The task of interpreting in more analytical terms what actually happened in those four days is unfinished. This essay argues that an understanding of the subjective viewpoint of the Filipino public is important because it provides a key to the problem whether and how far the people are prepared to support meaningful changes in Philippine society; notwithstanding the analysts and scholars who argue over the specific characteristics of the February uprising. Moreover, it emphasizes the ideological struggle that must be waged in order to preserve the democratic gains. Set in this context, it examines and evaluates Cory Aquino’s government in the face of lingering contradictions and formidable stumbling blocks.
Keywords: Philippine society; February uprising; democratic gains; ideological struggle; Cory Aquino